Alkaloids from leaves and bark of Alstonia scholaris in the Philippines - Yamauchi, Tatsuo (Archīum Ateneo, 1990)
Lagunamine (19-hydroxytubotaiwine), angustilobine B acid and losbanine (6,7-seco-6-nor-angustilobine B) were obtained from the leaves of PhilippineAlstonia scholaris, together with tubotaiwine, its oxide, and 6,7-seco- angustilobine B; the structures were determined from spectral evidence. 17-O-Acetylechitamine was isolated from the bark of the plant along with echitamine. Alkaloidal patterns in the leaves and barks of PhilippineA. scholaris are discussed in relation to those reported from the same plant growing in Asian continental districts.